Predicting the Irish "Gay Marriage" Referendum - Nikos Askitas (Institute for the Study of Labor (IZA), 2015)
On February 20 2015 Irish Premier Enda Kenny confirmed that a "yes-no" referendum on same sex marriage would be held on May 22 of the same year. A yes vote would legalise same sex marriage in Ireland. As the Irish premier put it, the vote was about "tolerance, respect and sensitivity". The electoral outcome turned out to be 62.07% for the yes vote with voter turnout at 60.52% of the registered voters. Ireland thus became the first country in the world to legalise same sex marriage through a popular vote. Using hourly Google Search data one week prior to the Irish Referendum of May 22 2015 and a simple ratio of "vote yes" to "vote no" searches I demonstrate how the outcome could have been predicted on the nose. The method is used here successfully for the second time and is so far as I know the only one which forecasts popular vote with Google Search.
Keywords: D72; G34; 330; referendum; predicting; Google Trends; Google Search; complexity; behaviour; data science; computational social science; complex systems